2015
DOI: 10.1016/j.devcel.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the Function of Metazoan Histones using Engineered Gene Clusters

Abstract: SUMMARY Histones and their post-translational modifications influence the regulation of many DNA-dependent processes. Although an essential role for histone-modifying enzymes in these processes is well established, defining the specific contribution of individual histone residues remains a challenge because many histone-modifying enzymes have non-histone targets. This challenge is exacerbated by the paucity of suitable approaches to genetically engineer histone genes in metazoans. Here, we describe a facile pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
280
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(317 citation statements)
references
References 62 publications
(86 reference statements)
16
280
3
Order By: Relevance
“…In addition, it will be important to determine whether H3K36 mono-or di-methylation are required for splicing in metazoa. With the availability of new Drosophila histone point mutant platforms, 43 it will be of interest to directly address the role of H3K36me in regulating canonical and alternative splicing in a metazoan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it will be important to determine whether H3K36 mono-or di-methylation are required for splicing in metazoa. With the availability of new Drosophila histone point mutant platforms, 43 it will be of interest to directly address the role of H3K36me in regulating canonical and alternative splicing in a metazoan.…”
Section: Discussionmentioning
confidence: 99%
“…36 Studies show that Set2 is associated with the elongating form of RNA Pol II and mediates H3K36me2/me3 to recruit a number of chromatin-modifying complexes (Rpd3S and Isw1b) that maintain a repressive chromatin environment that is resistant to pervasive transcription in the coding regions of genes. [37][38][39][40][41][42] Although a number of studies have shown that the human homolog of Set2, SETD2, is important for alternative splicing 31,33 and that H3K36 is essential for viability in drosophila, 43 the direct role of H3K36me3 and other methylation states (particularly H3K36me2) in both canonical and alternative splicing has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Suv4-20h1/ Suv4-20h2 double knock-out MEFs are sensitive to DNAdamaging agents and display an increased number of chromosomal breaks relative to control MEFs in response to DNA damage (13). In flies, Setd8 deletion is lethal, and the sensitivity of flies expressing the substitution mutant H4K20A to DNA damage requires further investigation (17,18,34). Overall, the data argue that H4K20 methylation plays an important and evolutionary conserved role in the DNA-damage response.…”
Section: H4k20me3mentioning
confidence: 99%
“…knock-out flies, in which 100% death at the larval stage is observed (17,18,34). Suv4-20h1/Suv4-20h2 double knockout mice are born at sub-Mendelian ratios, have significant perinatal death, and upon birth are noticeably smaller than control littermates (13).…”
Section: H4k20me3mentioning
confidence: 99%
“…PRC2 trimethylates histone H3 on Lys27 (H3K27me3), and the genomewide distribution of its H3K27me3 product is highly correlated with transcriptionally silent genes (5). Moreover, Drosophila harboring a histone H3K27R or H3K27A point mutation fails to silence PcG target genes, indicating that this modification is essential for silencing (6,7). The repressive effect of H3K27 methylation by PRC2 is thought to be due, in part, to direct blocking of H3K27 acetylation (H3K27ac) (8), a mark of active enhancers and promoters, because methyl-and acetyl modifications of the Lys e-amino group are mutually exclusive.…”
mentioning
confidence: 99%